The Effects of Ag Nanopaticles to the Production of Astaxanthin Algae with Different pH and Salinity Growth Conditions - Tan, Yong Man (2016)
Astaxanthin, a xanthophyll carotenoid which often been refer as “super-antioxidant” compare to other antioxidant like β-carotene and vitamin E. there are two type of astaxanthin in the current market which are the natural form from living organisms and synthetic form synthesized from petrochemical source. However, the mass production in the commercial scale has been a technical challenge. Among all the sources of natural astaxabthin, Haematococcus pluvialis is one of the best sources astaxanthin up to 3% of dry weight of biomass has been extracted. This green microalgae is able to produce astaxanthin as a secondary metabolite when encounter any stress conditions and appear as “red” stage of its life cycle. In my research, I was aiming to determine the effect of silver nanoparticle in the production of astaxanthin by Haematococcus pluvialis with optimal pH and salinity. The optimal pH and salinity were treated with silver nanoparticles powder at different concentrations to study the effect of silver nanoparticle. There were 5 different pH and salinity (NaCI) to be applied in order to find the optimal pH and salinity after 30 days of cultivation. The silver nanoparticle was used to treat both of the optimal pH and salinity obtained from the previous cultivation. The results showed that highest production of astaxanthin in different pH and salinity were pH7 and salinity 0.25% which is as obtained in previous research done by Sarada, et.al, 2002. The production of astaxanthin by H.pluvialis treated with Ag nanoparticle was found to be highest in 10ppm which is 3.26mg/L at day 30th of extract. Besides, the astaxanthin content decreases as the concentration of Ag nanoparticle increases. Ag nanoparticle seem to have inhibitory effect on microalgae cells in the higher concentration as reflected in cell density. In conclusion, silver nanoparticle have negative effect in promoting the production of astaxanthin in H. pluvialis even with optimal pH and salinity.